The book of mothers : how literature can help us reinvent modern motherhood - Mullins, Carrie (St. Martin's Press, 2024)
"This treasure trove for book lovers explores fifteen classic novels with memorable maternal figures, and examines how our cultural notions of motherhood have been shaped by literature. Sweet, supportive, dependable, selfless. Long before she had children of her own, journalist Carrie Mullins knew how mothers should behave. But how? Where did these expectations come from-and, more importantly, are they serving the mothers whose lives they shape? Carrie's suspicion, later crystallized while raising two small children, was that our culture's idealization of motherhood was not only painfully limiting but harmful, leaving women to cope with impossible standards--standards rarely created by mothers themselves. To discover how we might talk about motherhood in a more realistic, nuanced, and inclusive way, Carrie turned to literature with memorable maternal figures for answers. Moving through the literary canon--from Pride and Prejudice and Little Women to The Great Gatsby, Beloved, Heartburn, and The Joy Luck Club-Carrie traces the origins of our modern mothering experience. By interrogating the influences of politics, economics, feminism, pop culture, and family life in each text, she identifies the factors that have shaped our prevailing views of motherhood, and puts these classics into conversation with the most urgent issues of the day. Who were these literary mothers, beyond their domestic responsibilities and familial demands? And what lessons do they have for us today-if we choose to listen?"--